Wie ist Dein Leben in und um Marburg? Teilhabe von Frauen und Mädchen - ein Forschungs-Bericht - Gerner, Susanne (Büchner-Verlag, 2020)
The research report »How is your life in and around Marburg?« provides extensive insights into experiences of participation and exclusion in the lives of women and girls with impairments. The underlying study is based on qualitative individual and group interviews as well as on the collection of subjective maps. It was conducted in 2018 and 2019 at the Protestant University of Applied Sciences Darmstadt in cooperation with the Equal Opportunities Department of the University City of Marburg. The focus is on the experiences and perspectives of women and girls with learning disabilities as well as deaf women and girls. The publication is aimed at participants and contributors to the study, gender equality policy actors, academic experts, political decision-makers and representatives of practical institutions. It wants to address women and girls as experts of their lives, encourage them and make their concerns visible. The research report in simple language includes the study design, the implementation of the qualitative study, key findings and resulting recommendations for action for the municipality and local actors.